Sample-displacement correction for whole-pattern profile fitting of powder diffraction data collected in capillary geometry - Scarlett, N.; Rowles, Matthew; Wallwork, K.; Madsen, I. (BLACKWELL PUBLISHING, 2011)
Abstract: Recent in situ experimentation at the Australian Synchrotron resulted in the nucleation and crystallization of material on the walls of the capillary reaction vessels. This lining of the capillary walls, without filling the bulk of the capillary volume, produced an artefact in the diffraction data due to sample displacement across the capillary. In effect, the experiment was examining simultaneously two samples displaced by equal and opposite amounts from the diffractometer centre. This was exaggerated by the fact that large-diameter (1 mm) capillaries had been used in order to increase the total sample volume and hence maximize the amount of material formed and examined. The effect of this displacement was to shift the diffraction peaks simultaneously to both lower and higher angles than their `ideal' positions, causing peak splitting in many instances. A model has been developed which considers the sample as being effectively two flat plate samples, thus allowing for correction through the use of sample displacement. An additional problem resulted from the oriented growth of the material on the capillary walls, producing preferred orientation in the observed data. The correction model can also be extended to model such anisotropic peak splitting caused by this preferential orientation of the crystallites on the capillary wall.